AN IMPROVED EMBALMING PROCEDURE FOR PRESERVATION OF THE CADAVERS - Draz, Umar; Qureshi, Muhammad Imran (Journal of Ayub Medical College Abbottabad, 2000)
Background: In many respects the embalmment of dead bodies with Formaldehyde is harmful for the health of embalmers. Therefore, there is need to develop methods that are potentially less harmful. Methods: In this study we tried to develop a new method for embalmment which is less harmful. In this method we preserved five bodies with the help of a specially constituted solution containing Sodium Pentachlorophenate and Sorbitol besides other ingredients. Results: Our results were encouraging as all the five bodies were used in summer heat for more than two months without any problems.